Paradigma Dakwah Kultural: Dimensi Sufisme dalam Kontruksi Karakter Bima pada Pewayangan Jawa - Ahmad Hidayatullah (Jurnal Ilmu Dakwah, 2019)
Wayang as a pride of Javanese culture is well known not only for artistic dimension, but also for a spiritual dimension. It can be seen from a compositions of wayang characters, namely Bima. This research is a qualitative research that focuses on library research about Mahabharata books, Javanese culture (wayang), Walisongo, and dakwah. This research is data analysis that uses descriptive analysis, as an effort to describe and analyze the siprirtiual dimensions are manifested in aspects of dakwah and sufism in the construction of the Bima character. The results of this study indicate that the character of Bima shows the construction for dimensions of dakwah and Sufism. The dimension of dakwah lies in the process of islamization of Hindu that contained in wayang that finally changes the character and storyline of the wayang itself. While the dimension of Sufism is in the process of conveying the values of Sufism, such as in the depiction of the soul (nafs) and manunggaling Kawula Gusti in the Dewaruci play.